EFFECTIVENESS TEST OF WOUND HEALING ACTIVITY OF ETHANOL EXTRACT OF SEA GRAPE (CAULERPA RACEMOSA) GEL ON WISTAR RATS - HARYANTI, SRI; PUTRI, ATHIKA DARUMAS; MUTMAINAH; CAHYANI, MONICA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to investigate the effect of varying concentrations of ethanol extract of Caulerpa racemosa on the physicochemical properties of gel formulations and their efficacy as wound healing agents, given the plant’s reported antibacterial, antioxidant, and anti-inflammatory activities. Methods: The extraction of C. racemosa was carried out through maceration for 3 × 24 hours using 96% ethanol as the solvent. The resulting ethanol extract was incorporated into three gel formulations containing 0.4%, 1.0%, and 1.6% extract concentrations, respectively. The formulations were evaluated for physicochemical properties, including organoleptic characteristics, homogeneity, pH, spreadability, adhesion, and viscosity. Wound healing efficacy was assessed using a wound healing model in male Wistar rats, and statistical analysis was performed to determine the significance of observed differences. Additionally, in silico analysis was conducted to assess skin permeability (logKp) of the extract compounds. Results: Increasing the concentration of C. racemosa extract in the gel led to a decrease in pH, viscosity, and adhesion, while spreadability increased. Notably, at 1.6% extract concentration, the pH dropped from 7.99 to 4.62, and viscosity decreased from 54.669 cps to 13.629 cps. Wound healing time was significantly improved with higher extract concentrations: F1 (11.4 d), F2 (9.8 d), F3 (8.2 d), compared to the negative control (14.4 d) and the positive control (7.6 d). Statistical analysis showed a significant difference in healing times (p < 0.05), although no significant difference was observed between F3 and the positive control (p > 0.05). In silico findings indicated that most compounds in the extract had logKp values within the acceptable range for skin permeability (>-3.0 cm/s). Conclusion: The ethanol extract of C. racemosa influenced the physicochemical properties of gel formulations and enhanced wound healing activity in a concentration-dependent manner. A 1.6% concentration was found to be the most effective, showing wound healing efficacy comparable to that of the positive control, suggesting its potential as a natural alternative for topical wound healing treatment.